Formação profissional nos cursos de graduação em serviço social: pensamento e ação pedagógicos dos docentes - Moraes, Elivânia da Silva (2014)
The thesis presented here is mainly aimed to understand the epistemological and theoretical and practical frameworks of the national project of vocational training of social workers and its implementation in the organization and curriculum development of undergraduate courses in Social Work, focusing on educational thought and action of teachers. To achieve this objective investigative resorted to research qualiquanti using the Collective Subject Discourse methodology, which is based on the Theory of Social Representations (attribution of meaning of subjects), is based testimonies collected material verbal or written speeches. Interviews with teachers of Social Work courses in two social fields were carried out: the State University of Ceará (UECE) and the Metropolitan School of Fortaleza (FAMETRO) and document analysis in reference legal texts for training and activities of social workers in Brazil and courses investigated the theoretical framework of the research focused on three thematics: 1. Educational evaluation, based on the ideas Scriven (1966); Stake (1967), Guba and Lincoln (1989) and Saul (1995); 2. Curriculum and Curriculum Evaluation, we use us Giroux (1996), Apple (2006) and Leitinho (2000) and Teaching Practice, referring to the contributions of Zeichner (1992), Nóvoa (1992), Tardiff (2002) and Imbernon (1998). This investigative foray allows to realize that planning and curriculum development of social work graduate students investigated and the teaching practice that these are founded on a formal logic and an instrumental reason. This statement is dissonant with respect to the dialectic in which anchors the critical theory that gives character to training and interventional dimension of social worker today announced the National Project for Vocational Training in the legal framework of the profession and entered in the pedagogical projects of the courses of graduation